Analysis of C-Reactive Protein (CRP) Levels among Pulmonary Tuberculosis Patients in the Telaga Dewa Primary Health Care Area, Bengkulu City - Winda Novita; Putra Adi Irawan; Wiwit Sulistyasmi; Gani Asa Dudin (POLTEKKES KEMENKES BENGKULU, 2026)
Background : Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Pulmonary tuberculosis can be transmitted through droplets of saliva released by infected individuals when sneezing or coughing and can spread to others through the air. CRP (C-Reactive Protein) is a protein produced by the liver in response to inflammation in the body. In patients with pulmonary tuberculosis (Pulmonary TB), CRP levels often increase due to infection caused by Mycobacterium tuberculosis. Objective :This study aimed to determine the description of CRP (C-Reactive Protein) levels in patients with Pulmonary Tuberculosis (Pulmonary TB) in the working area of Telaga Dewa Public Health Center, Bengkulu City. Result : This study employed a descriptive design with total sampling involving 24 patients diagnosed with Pulmonary Tuberculosis (Pulmonary TB). The study was conducted at the Medical Laboratory Technology Department Laboratory, Health Polytechnic of the Ministry of Health Bengkulu. Based on the results, it was found that out of 24 samples, the majority (79.2%) of respondents had non-reactive CRP (C-Reactive Protein) results, totaling 19 individuals, while a small proportion (20.8%) had reactive CRP results, totaling 5 individuals. Conclusion : Most pulmonary TB patients showed non-reactive CRP results.